The Enigmatic Mushtikas and the Associated Triangular Terracotta Cakes: Some Observations - J. Manuel (Ancient Asia, 2010)
For over four decades, now, mushtikas and its common associate, the triangular terracotta cakes have been believed to be part of ‘fire altars’. This is, in spite of the fact that, either or both of these have been found from hearths, ovens, kilns, as flooring material, on walls, in passages, streets, bathrooms and therefore obviously near commodes. Further, the great variety of central stele and construction material, size and shape, materials found within ‘fire altars’ suggest that, all the above were devoid of religious symbolism and used to achieve domestic or industrial objectives. The cakes being primarily associated with run of the mill economic activities ended up in diverse and defiling contexts. However, like many cultures across time and space Harappans may also have used the medium of fire for offering sacrifices. Therefore the existence of ‘fire altars’ is not denied as such, but these then should not have the ubiquitous cakes, at the least.